Generalization of the H.A. Schwarz Theorem on Stability of Minimal Surfaces - Aminov, Yu.; Witkowska, J. (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна НАН України, 2007)
We proved two theorems on stability of minimal submanifolds in a Riemannian space, which can be included in a regular family of minimal submanifolds.